Factors Influencing the Students' Adoption of ELearning Among Commerce and Management Undergraduates: Evidence From University of Jaffna - Shivany, S.; Inthusha, S. (Sairam Institute of Management Studies, India, 2017)
This Study Focuses on Examining the Factors Affecting Student Adoption of E Learning. This Is Designed to Conduct Undergraduates of Faculty of Management Studies and Commerce, University of Jaffna. Based On Different Theories Especially Technological Adoption Theory and Empirical Evidences, Individual Characteristics, Individual Perception, Perceived Usefulness Perceived Ease of Use, ICT Infrastructure, Experience, Social Influence Institutional Support and the E-Learning Process Are Factors Identified. Advanced Multivariate Analysis as Exploratory Factor Analysis Is Utilized to Find Out the Factors Affecting Student Adoption Of E-Learning. There Are Four Factors Identified Through Exploratory Factor Analysis. Institutional Support, Individual Characteristics, Perceived Usefulness and Perceived Ease of Use Are Factors Identified Which Affect Student Adoption of E Learning. Therefore, Efforts to Improve E-Learning Adoption Should Concentrate on Improving Institutional Support, Individual Characteristics, Perceived Usefulness and Perceived Ease of Use. The Faculty Should Invest More on Infrastructure Such as in Fast and Reliable Internet Access and Provide a Dedicated Mirrored Server For E-Learning. The Faculty Should Also Integrate E-Learning into the Faculty Strategic Plan and Annual Work Plans and Develops a Clear Policy and Also Fund E-Learning Initiatives.
Keywords: E-Learning; Individual characteristics; Perceived Ease of Use and Perceived Usefulness